Public acceptance towards Kelantan gold dinar - Nik Maheran Nik Muhammad (2011)
This research was conducted in objective to identify the factors that influence public acceptance towards Kelantan gold dinar. For this purpose, survey to 220 respondents who bought Kelantan gold dinar at ar-rahnu (Kelantan gold dinar distribution centre) using purposive sampling method was conducted. Out of those, 100 questionnaires were received and usable. The data was then analyzed using SPSS statistical tool via frequency analysis, factor analysis, reliability test and descriptive analysis. From factor analysis it was found that there were four factors namely economic, political, investment and social factors that influenced the public acceptance towards Kelantan gold dinar. Descriptive analysis on the other hand found that an economic factor was the most influential factors followed by social, political and investment factor. The present study is descriptive in nature thus for future research, prescriptive research is recommended so that it can determine how gold dinar influences the economic stability. Future research could also be investigated focusing on the effectiveness of the gold dinar investment strategy and their implementation to increase economic stability.